Empire and Politics in the Eastern and Western Civilizations Searching for a 'Respublica Romanosinica' - Ahn, Jaewon; Balbo, Andrea; Kim, Kihoon (Roma Sinica, 2022)
The volume includes the proceedings of the 2nd Roma Sinica project conference held in Seoul in September 2019 and aims to compare some features of the ancient political thought in the Western classical tradition and in the Eastern ancient thought. The contributors, coming from Korea, Europe, USA, China, Japan, propose new patterns of interpretation of the mutual interactions and proximities between these two cultural worlds and offer also a perspective of continuity between contemporary and ancient political thought. Therefore, this book is a reference place in the context of the comparative research between Roman (and early Greek thought) and Eastern thought. Researchers interested in Cicero, Seneca, Plato, post-Platonic and post Aristotelic philosophical schools, history, ancient Roman and Chinese languages could find interesting materials in this work.